Impact of bariatric surgery on depression and anxiety symptons, bulimic behaviors and quality of life - Tae,Bárbara (2014)
OBJECTIVE: To assess psychiatric symptoms, substance use, quality of life and eating behavior of patients undergoing bariatric surgery before and after the procedure.METHODS: We conducted a prospective longitudinal study of 32 women undergoing bariatric surgery. To obtain data, the patients answered specific, self-administered questionnaires.RESULTS: We observed a reduction in depressive and anxious symptoms and also in bulimic behavior, as well as an improved quality of life in the physical, psychological and environmental domains. There was also a decrease in use of antidepressants and appetite suppressants, but the surgery was not a cessation factor in smoking and / or alcoholism.CONCLUSION: a decrease in psychiatric symptoms was observed after bariatric surgery, as well as the reduction in the use of psychoactive substances. In addition, there was an improvement in quality of life after surgical treatment of obesity.